Afebrile benign seizures associated to rotavirus gastroenteritis - Delgado Bocanegra, Ronald (2008)
Introduction: Rotavirus is the main cause of gastroenteritis in children under 3 years of age. Some reports have been published, describing cases of gastroenteritis associated to afebrile benign generalized seizures. These seizures occurring with mild dehydration and with no hydroelectrolytic imbalance have been frequently described in Asia, but they have rarely been reported in the rest of the world.Case report: A 1-year and two-months old male infant presented with tonic seizures associated with rotavirus gastroenteritis. The episode was self-limited and with a good outcome up to now. This condition is not exclusive to Asia and it may even be more frequent in our environment but misdiagnosed.Conclusion: to organization one does not appear exclusively in Asia and it is probable that in our means but frequent but it is subdiagnosed.